Pengaruh Digital Teknologi, Sosialisasi Perpajakan, dan Self Assessment System terhadap Kepatuhan Wajib Pajak - Fathia Azzahra; I Gede Adi Indrawan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to empirically test and analyze the partial and simultaneous influence of Digital Technology, Tax Socialization, and the Self-Assessment System on the Compliance of Individual Taxpayers (Wajib Pajak Orang Pribadi) registered at the KPP Pratama Tigaraksa, Tangerang Regency. This study is backgrounded by the phenomenon of electronic tax filing (e-filing) revenue inconsistencies, fluctuations in achieving the tax revenue targets at KPP Pratama Tigaraksa, and the existence of research gaps or result mismatches among previous studies. This study applies a quantitative approach with a descriptive survey method. The research population comprises all Individual Taxpayers registered at KPP Pratama Tigaraksa, totaling 99,927 taxpayers. By utilizing the Slovin formula with a 10% margin of error, a sample size of 100 respondents was selected using a probability sampling technique with a simple random sampling approach. Primary data was gathered through questionnaires distributed via Google Form and subsequently analyzed using Multiple Linear Regression analysis, processed through IBM SPSS 25. The empirical results of this research demonstrate that, simultaneously, Digital Technology, Tax Socialization, and the Self-Assessment System have a significant positive effect on Taxpayer Compliance. Partially, the statistical analysis reveals that Digital Technology does not have a significant effect on Taxpayer Compliance. Conversely, both Tax Socialization and the Self-Assessment System partially exert a positive and significant influence on Individual Taxpayer Compliance at KPP Pratama Tigaraksa.